THE USE OF COMPUTER-ASSISTED LANGUAGE LEARNING (CALL) TO TEACH ACADEMIC WRITING FOR HIGHER EDUCATION STUDENTS - Auladi, Ifan Rikhza; Hartono, Rudi; Wahyuni, Sri (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Computer-Assisted Language Learning (CALL) has become an important tool in modern language education, offering many advantages and some challenges. CALL allows flexibility, learner autonomy, and wider access to communication with teachers and peers, while also providing authentic materials that help with language acquisition. CALL is especially useful in improving writing skills, as it includes tools for spelling and grammar correction. However, there are also disadvantages, such as its complexity for users, high costs, and the lack of face-to-face interaction, which can hinder the learning process. There are also issues like limited internet access, distractions, and ineffective learning in some online contexts. Despite these drawbacks, the use of CALL in language learning, particularly for writing, has become necessary due to technological progress and the shift to online learning caused by the COVID-19 pandemic. This study explores the use of CALL in teaching academic writing, with a focus on writing abstracts. The participants are non-native speakers in their final year of an undergraduate civil engineering programme, aged between 21 and 23, with an elementary level of English proficiency. The aim is to improve students' understanding of academic writing, particularly the structure and content of abstracts, using CALL tools to aid the learning process. A text-oriented approach is applied, focusing on the simple present tense, paraphrasing techniques, and the use of CALL tools like Padlet and Quizizz. The learning process consists of pre-activities, classroom activities, and post-activities designed to develop students' writing skills. Although CALL provides flexibility and promotes learner autonomy, challenges such as limited vocabulary and reliance on machine translation were observed. To overcome these issues, guidance from instructors and active engagement in the learning process are crucial. Overall, CALL is a valuable tool in teaching writing, especially in digital learning environments.